PENGARUH RASIO DERAJAT DESENTRALISASI DAN PERTUMBUHAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PERTUMBUHAN EKONOMI KABUPATEN BENGKALIS - Fakhruddin, Imam; Saputra, Billy Yanis; Firdaus, Firdaus (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
Regional economic growth in Bengkalis Regency over the past decade has tended to move negatively, far below national economic growth. This research was conducted to determine and analyze the effect of the ratio of the degree of decentralization and the growth of PAD on the economic growth of Bengkalis Regency. The data in this study were sourced from the 2012-2021 Regional Financial and Asset Management Agency in the form of a Budget Realization Report (LRA) and Gross Regional Domestic Product of Bengkalis Regency for 2012-2021. Data were analyzed using SPSS Version 26.0 which was focused on descriptive variables and processed using multiple linear regression methods. The results showed that partially the degree of decentralization and PAD growth did not affect the economic growth of Bengkalis Regency.